1991
DOI: 10.1063/1.460480
|View full text |Cite
|
Sign up to set email alerts
|

Studies of electron collisions with polyatomic molecules using distributed-memory parallel computers

Abstract: Elastic electron scattering cross sections from 5-30 eV are reported for the molecules C H C 2 H 6 , C 3 Hs, Si 2 H 6 , and GeH 4 , obtained using an implementation of the Schwinger 2 4' multichannel method for distributed-memory parallel computer architectures. These results, obtained within the static-exchange approximation, are in generally good agreement with the available experimental data. These calculations demonstrate the potential of highly parallel computation in the study of collisions between low-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
6

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 37 publications
9
52
0
6
Order By: Relevance
“…Schwinger multichannel theoretical approach 54,55 reported corresponding cross sections for electron energies in the range 5 -30 eV. Generally quite good agreement was found between the results from these calculations and the data of Dillon et al, 53 so our recommended data in Table 21 below …”
Section: Si 2 Hsupporting
confidence: 74%
See 1 more Smart Citation
“…Schwinger multichannel theoretical approach 54,55 reported corresponding cross sections for electron energies in the range 5 -30 eV. Generally quite good agreement was found between the results from these calculations and the data of Dillon et al, 53 so our recommended data in Table 21 below …”
Section: Si 2 Hsupporting
confidence: 74%
“…Thereafter, the only comprehensive experimental study, which reported elastic DCS, ICS, and MTCS for energies between 1.5 and 100 eV and scattering angles of 10°-130°, was published by Dillon et al 58 Subsequently, a Schwinger multichannel theoretical approach 54 reported corresponding cross sections for electron energies in the range 5 -30 eV. Recently, two other calculations have also been reported.…”
Section: -20 Yoon Et Almentioning
confidence: 98%
“…In this procedure, the radial k-space is discretized on the quadrature points {k j }, where the g m μν (k j ) matrix elements are calculated, and the {k l } angular quadratures are also employed to obtain the g m μν elements, according to equation (35). While this numerical integration is significantly more demanding than the previous implementation based on a numerically complete single-particle space, it provides a faster convergence with respect to the Gaussian basis sets and proved to be more stable and reliable over a large number of applications.…”
Section: Numerator and Green's Operator Matrix Elementsmentioning
confidence: 99%
“…Historically, the evolution of the method went through the following steps: (1) Cartesian Gaussian insertion with the computer code running in central memory [30,31]; (2) numerical integration of the residue part of the V G (+) P V term 2 ; (3) NASA's reorganization of the computer codes aiming at intense use of I/O (disk memory instead of central memory) [33,34]. From this point two different versions of the program evolved in different ways, the version at Caltech bet on: (4) parallelization of the computer codes [35]; while the version at the State University of Campinas (UNICAMP) returned to a central memory strategy and bet on: (5) the use of norm-conserving pseudopotentials (SMCPP) [36]; both versions relied on a (6) three-dimension integration of the V G (+) P V term [37]. From this point, the Brazilian version that produced the results described in this paper evolved to: (7) single excitation configuration interaction for the target description of the excited states and a strategy of a minimal orbital basis for single configuration interaction (MOBSCI) [38] for choosing the appropriate and feasible level of multichannel coupling computation; and finally moved to (8) consolidation of the central memory strategy with parallelization of the computer codes with all properties cited above [39].…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a computational method, the Schwinger Multichannel or SMC method [2,3], that is specifically intended to treat inelastic as well as elastic collisions of low-energy electrons with polyatomic molecules, and we have adapted the SMC method to run efficiently on parallel computers [4,5,6,7], which provide the resources necessary to carry out large-scale computations. We have applied the parallel SMC method to obtain elastic and inelastic electron cross sections for a variety of molecules, with generally good results [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%